Formal Verification of Nonfunctional Requirements of Overall Instrumentation and Control Architectures - Polina Ovsiannikova; Antti Pakonen; Dmitry Muromsky; Maksim Kobzev; Viktor Dubinin; Valeriy Vyatkin (IEEE Open Journal of the Industrial Electronics Society)
The design of safety-critical cyber–physical systems requires a rigorous check of their operation logic, as well as an analysis of their overall instrumentation and control (I&C) architectures. In this article, we focus on the latter and use formal verification methods to reason about the correctness of an I&C architecture represented with an ontology, using the example of a nuclear power plant design. A safe nuclear power plant must comply with the defense-in-depth principle, which introduces constraints on the physical and functional components of the I&C systems it consists of. This work presents a method for designing nonfunctional requirements using function block diagrams, its definition using logical programming, and demonstrates its implementation in a graphical tool, FBQL. The tool takes as input an ontology representing the I&C architecture to be checked and allows visual design of complex nonfunctional requirements as well as explanation of the results of the checks.